(untitled) (Research, Society and Development, 2022)
The use of technology in education provides a very wide range of options that help in the teaching-learning process, helping contents be understood more effectively, as long as the student is oriented, as well as having prior knowledge in relation to the subject that will be explored. This time, the present study aims to illustrate how the use of information and communication technologies has contributed to the teaching-learning process of Physics contents. This is an experience report of a descriptive nature with a qualitative approach based on educational practices carried out in the subject of Physics. The participants were students from the 9th year of elementary school to the 2nd year of high school, aged between 14 and 17 years old, all belonging to private sector schools, located in the state of Sergipe. Classes took place before and during the pandemic, that is, they were held in person and remotely. The teaching of Physics with the use of technological interfaces became a positive point in the teacher’s school life, given that the classes were less stressful, without parallel conversations, as well as the subjects were better understood by the students. There was greater participation, curiosity, reasoning and fewer difficulties in understanding concepts, calculations and formulas.